A Case Study of Congklak Playing Therapy in Children to Improve Social Interaction Due to Gadget Addiction - Ahmad, Nizar; Firmansyah, Andan; Setiawan, Henri (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2024)
Objective: To see the effectiveness of congklak play therapy in increasing social interaction in children because of gadget addiction. Method: The research design used is a case study research method, with a descriptive research type. The research subject used was 1 school-age child client with social interaction problems due to gadget addiction. Result: Subjectively, the client experiences an increase in interaction with the people around him and a decrease in the intensity of his use of gadgets. Clients can better control their emotions, and there is an increase in learning. Likewise, objectively, the client seems to be able to control his emotions, and often interacts with the people around him.  Conclusion: After doing research on An. M., the data obtained by the client's mother complains that the client rarely interacts with other people; the client often plays gadgets until he forgets the time; and when the gadget is taken, he often gets angry. The client's mother gets information from the client's school teacher that the client is less cooperative while studying at school. Based on the assessment, the diagnosis that emerged was social interaction disorder. The author conducted an intervention to overcome social interaction disturbances for four days. The intervention that the author has done is to provide congklak play therapy. After the intervention, the client's signs and symptoms of impaired social interaction diminished. The client has often interacted with people around him by using his gadget a little less.